2021
DOI: 10.3389/fspor.2021.671764
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training With Partial Blood Flow Restriction in a 99-Year-Old Individual: A Case Report

Abstract: In aging populations for which the use of high loads is contraindicated, low load resistance training associated with blood flow restriction (RT-BFR) is an alternative strategy to induce muscle mass gains. This study investigates the effects of RT-BFR on muscle mass, muscle function, and quality of life of a 99-year-old patient with knee osteoarthritis and advanced muscle mass deterioration. Training protocol consisted of 24 sessions of a unilateral free-weight knee extension exercise associated with partial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Another study reported that after 24 sessions of resistance training with blood flow restriction (BFR), a 12% increase in muscle cross-section and an 8% increase in lateral extensor muscle thickness were observed in 90-year-olds. Finally, the researchers identified resistance training with BFR as an effective strategy for improving muscle mass and quality of life ( 12 ). In this study, we intend to investigate the effects of sarcopenic obesity and exercise on the mechanisms of myocytes and adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that after 24 sessions of resistance training with blood flow restriction (BFR), a 12% increase in muscle cross-section and an 8% increase in lateral extensor muscle thickness were observed in 90-year-olds. Finally, the researchers identified resistance training with BFR as an effective strategy for improving muscle mass and quality of life ( 12 ). In this study, we intend to investigate the effects of sarcopenic obesity and exercise on the mechanisms of myocytes and adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“… 151 In a study conducted by Scarpelli et al, it was implemented on a 99-year-old patient with knee osteoarthritis and secondary sarcopenia. 152 After 24 sessions of treatment, the lateral femoris muscle exhibited a 12% increase in cross-sectional area, an 8% increase in thickness, and an improvement in quality of life based on a questionnaire score. The utilization of electrical stimulation to enhance muscle function and facilitate weight has gained popularity in recent years.…”
Section: Other Non-pharmacological Strategiesmentioning
confidence: 97%
“…Indeed, there may even be clinical scenarios where the practice of heavy-load training is contraindicated such as in early rehabilitation for acute tendinopathies or tendon rupture, or in patients who are frail, elderly or have significant medical co-morbidities [260]. The 'one-size-fitsall' approach to tendinopathy rehabilitation of prescribing heavy-load resistance training which has become widespread in recent years, is an unrealistic and potentially counterproductive and detrimental practice [261]. There is significant heterogeneity which exists within tendinopathy as a disease entity and in its environmental and clinical presentation, due to the unique individual factors and circumstances of each patient [262].…”
Section: Clinical Implications and Practical Applicationmentioning
confidence: 99%